Ottomans and Armenians : a study in counterinsurgency - Erickson, Edward J., 1950- 1950- (Palgrave Macmillan, 2013)
"This is a military history of Armenian insurrection in the Ottoman Empire from 1890-1915 and the evolution of an Ottoman counterinsurgency response. It describes the growth and activities of the Armenian revolutionary committees in the context of empire-wide insurgency. At the beginning of the First World War, the Ottoman government believed that the Armenian revolutionary committees directly threatened the empire's military lines of communications which were weakened by the concentration of the Ottoman army on the front lines away from the empire's core areas. In 1915, the Ottoman government pursued a counterinsurgency campaign against the Armenian revolutionary committees from a position of constrained resources, resulting in a strategy of population relocation explicitly designed to separate insurgents from a base of support in a narrowly defined area. Using archival sources, the book establishes a comprehensive framework for understanding why the Ottoman state relocated the Armenian population of six Anatolian provinces in 1915 but did not relocate Armenians living elsewhere in the empire"..